Learning The Fiqh of Salat Using The Deep Learning Approach to Improve The Religious Character of Elementary Education Students - Katni Katni; Luthfida Zulfa Fathiasani; Athaariq Deyan Fadhilah; Aulia Intan Maharani; Iis Munawaroh; Shofiyah Hestiqomah (Assyfa Journal of Islamic Studies, 2025)
Learning the jurisprudence of prayer occupies a fundamental position in Islamic education at the elementary level because prayer is the main worship that serves as a pillar of religion and a means of forming the spiritual and moral character of students from an early age. The problem of teacher-centered fiqh learning is evident in the dominant role of the teacher in delivering the material, while students tend to be passive listeners without active involvement in the learning process. This condition causes fiqh learning to be more oriented towards memorizing concepts and conveying theories rather than understanding the meaning and practice of worship in depth. This study aims to analyze the application of the Deep Learning approach in learning the jurisprudence of prayer and its implications for improving the religious character of students at Madrasah Ibtidaiyah Muhammadiyah 3 Ponorogo. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the Deep Learning approach was able to create more meaningful, active, reflective, and contextual learning about the jurisprudence of prayer through direct practice, reflective discussions, and the habituation of daily worship. This learning has an impact on improving students' religious character as demonstrated through discipline in worship, prayer habits, polite attitudes, and increased spiritual awareness in everyday life. Successful implementation of learning is supported by the madrasa's religious culture, teacher competence, adequate worship facilities, and active student involvement. While inhibiting factors include limited learning time, differences in student characteristics, and lack of family support. Thus, the Deep Learning approach to teaching Islamic jurisprudence (fiqh) prayer can be positioned as an effective Islamic education model for holistically shaping students' religious character.